English-learning stress and performance in Chinese college students: A serial mediation model of academic anxiety and academic burnout and the protective effect of grit - Xu, Liling; Wang, Zhenhai; Tao, Zhiyuan; Yu, Chengfu (Frontiers in Psychology, 2022)
Introduction Having to adapt to a new environment with various other challenges while completing their studies, Chinese college students experience intense stress related to the study of the English language. However, there has been little research on the serial mediating mechanism of English-learning stress on English academic performance. Methods Present study recruited 1130 undergraduate students to finish self-report online questionnaire to collect the information about their English-learning stress, academic anxiety and burnout, English academic performance and grit. We constructed a moderated serial mediation model to test the effect of academic anxiety and academic burnout and explored whether grit can restrict the decrease in academic performance caused by English-learning stress. Results Results show that: (1) both academic anxiety and academic burnout mediate the relationship between English-learning stress and performance; (2) academic anxiety and academic burnout show a significant serial mediating role between academic pressure and English academic performance; and (3) grit significantly moderates the relationship between academic burnout and English academic performance. Discussion These results lead us to believe that cultivating the grit of Chinese college students may be an effective way to improve the academic performance of those experiencing high English-learning stress.